POLARIZATION EFFECTS ON THE STRUCTURE AND DYNAMICS OF IONIC MELTS - Wilson, M; Madden, P (1994)
The effect of induced dipoles on the structure and dynamics of melts of stoichiometry MX 2 is discussed. Interest centres on the case of M being a small, highly polarizing cation and X a highly polarizable anion. It is shown that 'covalent' effects on the short range structure and the appearance of a pre-peak in the structure factor may be explained within a purely ionic model. A connection between these structural features and the dynamical properties of 'strong' liquids is suggested.